TGF-β-induced fibrosis: a review on the underlying mechanism and potential therapeutic strategies - Ong, Chun Hao; Tham, Chau Ling; Harith, Hanis Hazeera; Firdaus, Nazmi; Israf, Daud Ahmad (Elsevier, 2021)
Transforming growth factor-beta (TGF-β) plays multiple homeostatic roles in the regulation of inflammation, proliferation, differentiation and would healing of various tissues. Many studies have demonstrated that TGF-β stimulates activation and proliferation of fibroblasts, which result in extracellular matrix deposition. Its increased expression can result in many fibrotic diseases, and the level of expression is often correlated with disease severity. On this basis, inhibition of TGF-β and its activity has great therapeutic potential for the treatment of various fibrotic diseases such as pulmonary fibrosis, renal fibrosis, systemic sclerosis and etc. By understanding the molecular mechanism of TGF-β signaling and activity, researchers were able to develop different strategies in order to modulate the activity of TGF-β. Antisense oligonucleotide was developed to target the mRNA of TGF-β to inhibit its expression. There are also neutralizing monoclonal antibodies that can target the TGF-β ligands or αvβ6 integrin to prevent binding to receptor or activation of latent TGF-β respectively. Soluble TGF-β receptors act as ligand traps that competitively bind to the TGF-β ligands. Many small molecule inhibitors have been developed to inhibit the TGF-β receptor at its cytoplasmic domain and also intracellular signaling molecules. Peptide aptamer technology has been used to target downstream TGF-β signaling. Here, we summarize the underlying mechanism of TGF-β-induced fibrosis and also review various strategies of inhibiting TGF-β in both preclinical and clinical studies.